Social Security and Individual Welfare: Precautionary Saving, Borrowing Constraints, and the Payroll Tax - Hubbard, R. Glenn; Judd, Kenneth L. (American Economic Review, 1987)
This paper examines the impact of Social Security on national saving and individual welfare in the presence of realistic capital market imperfections–market failure in the private provision of annuities and restrictions on borrowing against anticipated future wages. The introduction of Social Security increases lifetime welfare and reduces national saving if borrowing restrictions are absent. However, the increase in individual welfare is reduced, and in some cases eliminated, when borrowing constraints are taken into consideration. The substantial difference suggests the importance of reexamining the proportional payroll tax finance of Social Security.